THE ROLE OF FORENSIC ENTOMOLOGY IN ESTIMATING THE TIME OF DEATH - Reqgi First Trasia (Bahasa Indonesia, 2022)
It takes dedication and thoroughness in uncovering the various mysteries behind forensic cases. Various methods will be needed in answering various questions related to these cases, and it is imperative that the evidence or expert testimony is can be accounted for. Over time, some of the evidence, especially human body tissue will undergo a process of degradation and eventually disappear. However, for a forensic entomologist, the damage and loss of body tissue can bring new evidence. Evidence which of course can be justified scientifically at court. Like when alive, the tissues of the human body after death remain attractive to them various types of insects. Different types of insects will be attracted at different stages from the decay stages of human tissue. These insects follow a development patterns. Related to knowledge about growth and development them, it can be used to make an estimate of how long it has been since the body has been dead. In addition, the identification of the above will also indicate whether a corpse has been moved from one area to another.